ANALISIS DAMPAK KEBIJAKAN PEMBANGUNAN BANDARA JENDERAL BESAR SOEDIRMAN DI KABUPATEN PURBALINGGA - Marthalina Marthalina; Syaiful Hukamak Ichsan (Post Graduate School of Government Science, 2022)
Development is intended to change the situation for the better according to the plan. From the point of view of development organizers, development goals are considered appropriate and appropriate if they have a positive impact on the community. The construction of the JB Soedirman airport is an urgency for the people of Central Java and requires good coordination between the government, the private sector and the community. This study will describe the impact of the construction of the JB Soedirman airport for the people of Purbalingga Regency. This study uses a descriptive qualitative method which is carried out directly in the field to find sources of data needed in solving problems. Research is also carried out with an inductive approach to look at facts and data that are specific in nature to draw general conclusions using laws and theories. Data was collected by observation, interviews, and independent documentation. The construction of JB Soedirman has had both positive and negative impacts on society and the economy. In addition to the Central Java Provincial Government and Purbalingga Regency Government who will benefit greatly from the presence of JB Soedirman, the local community is also expected to feel the impact of the development. The positive impact of the construction of the JB Soedirman airport can be seen from the economic aspect which is marked by the growth of economic activities, such as tourism, lodging, services and culinary. Changes also occurred in the territorial aspect of the area which was originally not too crowded, but gradually became denser with the start of airport operations and the creation of new jobs. The negative impact of the existence of JB Soedirman occurs in the social aspects of the community who experience cultural